Point mutations in a nucleoside transporter gene from Leishmania donovani confer drug resistance and alter substrate selectivity - Vasudevan, Gayatri (The National Academy of Sciences, 2001)
Leishmania parasites lack a purine biosynthetic pathway and depend on surface nucleoside and nucleobase transporters to provide them with host purines. Leishmania donovani possess two closely related genes that encode high affinity adenosine-pyrimidine nucleoside transporters LdNT1.1 and LdNT1.2 and that transport the toxic adenosine analog tubercidin in addition to the natural substrates. In this study, we have characterized a drug-resistant clonal mutant of L. donovani (TUBA5) that is deficient in LdNT1 transport and consequently resistant to tubercidin. In TUBA5 cells, the LdNT1.2 genes had the same sequence as wild-type cells. However, because LdNT1.2 mRNA is not detectable in either wild-type or TUBA5 promastigotes, LdNT1.2 does not contribute to nucleoside transport in this stage of the life cycle. In contrast, the TUBA5 cells were compound heterozygotes at the LdNT1.1 locus containing two mutant alleles that encompassed distinct point mutations, each of which impaired transport function. One of the mutant LdNT1.1 alleles encoded a G183D substitution in predicted TM 5, and the other allele contained a C337Y change in predicted TM 7. Whereas G183D and C337Y mutants had only slightly elevated adenosine K(m) values, the severe impairment in transport resulted from drastically (≈20-fold) reduced V(max) values. Because these transporters were correctly targeted to the plasma membrane, the reduction in V(max) apparently resulted from a defect in translocation. Strikingly, G183 was essential for pyrimidine nucleoside but not adenosine transport. A mutant transporter with a G183A substitution had an altered substrate specificity, exhibiting robust adenosine transport but undetectable uridine uptake. These results suggest that TM 5 is likely to form part of the nucleoside translocation pathway in LdNT1.1